A community-centred approach to global health security: implementation experience of community-based surveillance (CBS) for epidemic preparedness. Issue 1 (1st January 2020) - Byrne, Abbey; Nichol, Bronwyn
ABSTRACT: Background : Communities have a key role to play in global health security. The Red Cross/Red Crescent epidemic preparedness programme empowers volunteers and communities to: identify risks; recognise and notify epidemic alerts; take early action to control disease. The programme set out to establish community-based surveillance (CBS) as a preparedness model – yielding earlier detection and action to halt outbreaks at the outset. This paper reports on the mid-stage CBS implementation experience and results in Indonesia, Kenya, Sierra Leone and Uganda. Methods: Volunteers detect potential epidemic alerts and report immediately by mobile apps. The receiving supervisor cross-checks the alert and enters in a real-time database triggering response actions. Supervisors report to local authorities, integrating CBS alerts as notifications into national disease surveillance systems. Results: To develop health literacy and trust, volunteers achieved over 390, 000 instances of contact with people; 70, 000 house visits; 547 school health activities; and 17 radio shows. Volunteers are placed with wide geographic coverage and their weekly 'zero' reporting of 63%-83% indicates maintenance of the CBS system. The average accuracy of volunteers to identify alerts matching community case definitions is high in Sierra Leone 96%, Indonesia 90%, and Uganda 73%, however low in Kenya at 35%. Timeliness rates were high across all countries. Alerts were detected and notified to authorities within the targeted 24 hours at an average of 94%. Challenges and risks have related to: securing free SMS channels for alerts, time required for contextualised design, ensuring response action, and managing expectations of the scope of CBS. Conclusion: Early-stage results show positive impact and feasibility of preparedness CBS in high-risk zones to prevent large-scale outbreaks. Community engagement, stage-wise capacity building, monitoring and response actions, and collaborative relationships with stakeholders are important programme components for effectiveness. Communities themselves can be central change agents in global health security.